Two novel Tuber species (Tuberaceae, Pezizales) from southwestern China based on morphological and molecular evidence - Tian-Jun Yuan; Hong-Mei Luo; Kai-Mei Su; Shu-Hong Li; E-Xian Li (MycoKeys)
Based on morphological and molecular phylogenetic analyses, two new species, Tuber marroninum and Tuber conditum, belonging to the Latisporum group, were described from Yunnan province of southwest China. Morphologically, Tuber marroninum is distinguished from other Latisporum species by whitish and glabrous ascomata and a two-layered peridium, measuring 150–200 µm in total thickness, with an outer layer ranging from 40–60 µm. Tuber conditum is diagnosed by its thinner peridium (120–200 µm) and larger ascospores (49–66.5 × 34.5–60 μm in one-spored asci). According to the outcome of the ITS rDNA sequence analysis, the species of T. marroninum and T. conditum each form a distinct and well-supported group within the Latisporum group, respectively.